Brain-Washing In Red China - Hunter, Edward (Toronto Copp Clark Company, Ltd., 1951)
This material was tathered in the Far East and Southeast Asia during 1950 and 1951. I have made generous use of excerpts from articles of mine which appeared in the Miami Daily News and The New Leader magazine, for which I thank them.
Keywords: Fiction